2013
DOI: 10.1002/joc.3642
|View full text |Cite
|
Sign up to set email alerts
|

Climate change in the Tibetan Plateau Three Rivers Source Region: 1960-2009

Abstract: Changes observed in nine meteorological variables obtained from the Three Rivers Source Region (TRSR) between 1960 and 2009 were investigated using a fitted linear model, Mann-Kendall test, moving t-test, and Morlet wavelet. Analysis of the regionally scaled annual series from 1960 to 2009 showed that minimum (T min ), maximum (T max ), mean (T mean ) air temperature, precipitation (P ), potential evaporation (E p ), and sunshine hours (SH ) increased while relative humidity (RH ) and wind speed (W ) decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(70 citation statements)
references
References 78 publications
(121 reference statements)
5
65
0
Order By: Relevance
“…By contrast, temperature increase slowed down during the growth season after 2001. Although climate warming was aggravated after the 21st century in the TRSR, such warming was mainly contributed by higher temperatures during winter (Xu et al, 2011;Liang et al, 2013). Harris (2010) suggested that vegetation was least affected by temperature when it was dormant in winter compared with other growth stages in the Qinghai-Tibetan Plateau.…”
Section: Discussionmentioning
confidence: 98%
“…By contrast, temperature increase slowed down during the growth season after 2001. Although climate warming was aggravated after the 21st century in the TRSR, such warming was mainly contributed by higher temperatures during winter (Xu et al, 2011;Liang et al, 2013). Harris (2010) suggested that vegetation was least affected by temperature when it was dormant in winter compared with other growth stages in the Qinghai-Tibetan Plateau.…”
Section: Discussionmentioning
confidence: 98%
“…Tukey-Kramer comparisons between sites: Poisoned Site versus On Burrow = P \ 0.001; Poisoned Site versus On Colony = P \ 0.004; On Colony versus On Burrow = P \ 0.001 moisture data) and the extremely complex geology of the QTP, the additive impacts of an increased infiltration rate across the range of the plateau pika (nearly the entire QTP; Smith et al 1990;Smith and Xie 2008) on both groundwater retention and runoff control could be large and should be taken into consideration by policy-makers. Many contemporary factors enter into the hydrological profile on the QTP, including changes in grazing intensity, fencing, ''ecological migration,'' and climate change (Bauer 2005;Yan et al 2005;Yeh 2005;Foggin 2008;Xu et al 2009;Immerzeel et al 2010;Liang et al 2013;Yang et al 2014). The difference in runoff potential between poisoned and un-poisoned areas should be considered contributory to these factors.…”
Section: Discussionmentioning
confidence: 99%
“…2) was common for all meteorological stations in the TP, with the exception of significant common downward trends of Lenghu, Menyuan, Geermu, Xining, and Maduo in winter at deep. P decreased from the southeast to the northwest in the TP area owing to the soaring mountains that blocked moisture entering (Liang et al 2013). The proportion of summer P in annual P exceeded 60% for all meteorological stations in the TP.…”
Section: Statistical Information Of Meteorological Variables In Annuamentioning
confidence: 94%